Conceptual Framework of Make in India Campaign and It's Impact on Indian Economy - Gautam, Kamlesh Babu (Journal of Commerce and Trade, 2021)
Make in India is an international marketing campaigning slogan coined by the Prime Minister of India, Narendra Modi to attract businesses from around the world to invest and manufacture in India. The campaign has been concentrated to fulfill the purpose of Job Creation, Enforcement to Secondary and Tertiary sector, Boosting national economy, converting India to a self-reliant country and to give the Indian economy global recognition. Make in India which is the recipe of PM Narendra Modi's aims to make India the manufacturing hub of the world. The idea of utilizing cheap labor to produce for the world is not new. The Indian government through this initiative aims to put to use its rapidly increasing workforce to productive use, realizing that service sector though contributing about 55-60% of the GDP cannot be the sole driver of the economy. In this research paper `Make in India' an attempt has been made to review the pros and cons of this concept and to understand the impact of it on the Indian Economy. Make in India mission is one such long term initiative which will realize the dream of transforming India into manufacturing hub. Make in India campaign also focuses on producing products with zero defects and zero effects on environment. Come Make in India, Come Manufacture in India, Sell in any country of the world but manufacture here. We have got skill, talent, discipline and determination to do something. Classification-JEL : A11, E2